Influence Theory with Behavioral Counseling Lesson Study Through Modeling Techniques to Improve The Character Receives Advice from Others to Students - Nengah Dessy Martini; Nyoman Dantes; I Ketut Dharsana (International Conference on Technology and Educational Science)
This study aims to Determine the effectiveness of behavioral counseling by modeling techniques to improve the properties of being able to accept the advice of others. This type of research is quasi-experimental, pretest-posttest design with control group sample using modeling research design. The techniques. Collecting the data using a questionnaire that tested the validity and reliability, to test the hypothesis used t-test. This is evidenced by the value of the indicator properties of being able to accept advice from others (tcount 65,64 > ttable1,675) So that Ha is accepted. There are significant differences, the value of the student questionnaire before and after the service given. It was concluded that effective behavioral counseling with modeling techniques to improve the properties of being able to accept the advice of others.